Conventional and Advanced Lipid Parameters in Premature Coronary Artery Disease Patients in India - Sanjiv Kumar Bansal; Sarita Agarwal; Mridul Kumar Daga (Journal of Clinical and Diagnostic Research, 2015)
Background: Coronary artery disease (CAD) is the leading cause of death worldwide and has assumed alarming proportions in India with gradual increase in its incidence and prevalence over the last decade. India is in the middle of epidemic of coronary artery disease which is leading cause of hospital admissions, morbidity and mortality. In the Indian population, there is higher tendency to develop CAD at a younger age, which cannot be explained on the basis of conventional lipid parameters. Aim: The purpose of this study is to find advanced lipid parameters which correlate better with premature CAD, as compared to the conventional lipid parameters. Materials and Methods: Thirty middle aged individuals suffering from premature CAD and 30 age and gender matched healthy individuals without any history of clinical evidence suggestive of CAD were studied. Fasting venous blood samples of all the subjects under study were collected after an overnight fasting and conventional lipid parameters and advanced lipid parameters (i.e. oxidized LDL, Lp (a), ApoA-1, small dense LDL, ApoB) were estimated. Correlation of conventional and advanced lipid parameters with premature CAD and among each other was calculated using Pearson correlation coefficient. Results: In our study the values of ox-LDL, sdLDL, Lp (a) and ApoB, total cholesterol, TG, LDL-C were significantly higher while HDL-C and Apo A1 and were significantly lower in cases than in controls. Advanced lipid parameters have higher correlation with premature CAD as compared to conventional lipid parameters. OxLDL show the highest correlation coefficient (r=+0.89) among these parameters followed by Lp (a) (r=+0.86) and ApoB (r=+0.79). Conclusion: Advanced lipid parameters (i.e. oxidized LDL, Lp (a), ApoA-1, small dense LDL, ApoB) are better discriminator of premature CAD as compared to conventional lipid parameters (total cholesterol, triglycerides, low density lipoprotein and high density lipoprotein). Oxidised LDL, small dense LDL and lipoprotein (a) can explain occurrence of CAD in normolipidemic patients and proved to be better markers for explaining high degree of prematurity, morbidity and mortality of CAD in Indian population. They can prove to be better marker for early detection and intervention in premature CAD and site for targeted drug therapy.